A Review of Geoffrey M. Hodgson, Conceptualizing Capitalism: Institutions, Evolution, Future - Rose-Ackerman, Susan (Journal of Economic Literature, 2017)
Capitalism and law go together in Geoffrey M. Hodgson's comprehensive analysis of the intellectual history and practical development of the capitalist system in Western Europe and North America. Given the breadth and depth of Professor Hodgson's reading in political economy and his reflections on its implications for the present and future of global capitalism, his book deserves to be widely read. Labeling his approach legal institutionalism, he argues that a legal system that supports capitalism and the market is necessary but not sufficient to sustain a fair and efficient economic system. The state makes efficient markets possible, but it must also deal with the inevitable tensions and the fundamental asymmetry between labor and capital. Tensions arise because labor cannot be used as collateral for the loans that are needed for large-scale capitalist enterprise. Hodgson has not developed the political implications of his conclusions in any detail, but his work ought to inspire research that explores the implications of his arguments for ongoing projects of nation building. (JEL D72, K10, O43, P14, P16)